Risk Habitat Megacity - Heinrichs, Dirk (SpringerLink Bücher, 2012)
Foreword -- Part I: A Challenge for Research and Implementation -- Part II: Developing the Conceptual Framework -- Part III: Exploring Policy Fields -- Part IV: Synthesis and Perspectives